Effect of larval-stage mealworm (Tenebrio molitor) powder on qualities of bread - Khuenpet, K.; Pakasap, C.; Vatthanakul, S.; Kitthawee, S. (International Journal of Agricultural Technology, 2020)
Wheat flour without addition of larval-stage mealworm powder (control) had the highest peak viscosity of 139.14 RVU. The addition of higher levels of larval-stage mealworm powder resulted in significantly decrease in peak viscosity of wheat flour (p<0.05). The pasting temperatures of all samples were between 87.20 and 89.50oC. The hardness of bread without the addition of larval-stage mealworm powder was 108.50 gforce, whereas the hardness of fortified bread samples raised approximately 4 times when adding larval-stage mealworm powder to 5-15% (425.83 to 487.67 gforce). It was found that an increase of larval-stage mealworm powder leading to lower specific volume and higher hardness in bread after baking. The fortification of larval-stage mealworm powder also caused the increase of color intensity due to the original brown color of larval-stage mealworm powder and the occurrance of maillard reaction during baking. The non-uniformity of porosity of the bread products was observed in fortified bread samples. The bread products added by larval-stage mealworm powder at 0, 5, 10 and 15% of wheat flour had protein contents of 9.63, 12.63, 13.21 and 13.73% respectively. The bread products fortified at 5% of wheat flour revealed the most comparable quality to the control bread sample.